2010
DOI: 10.1007/s00125-010-1796-7
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, prediabetes and cancer mortality

Abstract: Aims/hypothesis We aimed to investigate the risk of cancer mortality in relation to the glucose tolerance status classified according to the 2 h OGTT. Methods Data from 17 European population-based or occupational cohorts involved in the DECODE study comprising 26,460 men and 18,195 women aged 25-90 years were collaboratively analysed. The cohorts were recruited between 1966 and 2004 and followed for 5.9 to 36.8 years. Cox proportional hazards analysis with adjustment for cohort, age, BMI, total cholesterol, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
155
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 51 publications
5
155
2
4
Order By: Relevance
“…Furthermore, we studied several factors proposed to mediate associations of diabetes and cancer. 31 The generalizability of our findings to populations in economically developed Western countries is supported by broadly consistent results across 97 prospective cohorts in 25 countries. Even though the 6% overall prevalence of diabetes in our study was somewhat lower than the prevalence currently reported for some Western populations, this difference would not have influenced hazard ratios.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, we studied several factors proposed to mediate associations of diabetes and cancer. 31 The generalizability of our findings to populations in economically developed Western countries is supported by broadly consistent results across 97 prospective cohorts in 25 countries. Even though the 6% overall prevalence of diabetes in our study was somewhat lower than the prevalence currently reported for some Western populations, this difference would not have influenced hazard ratios.…”
Section: Discussionsupporting
confidence: 69%
“…Epidemiology studies revealed that DM increased the incidence of HCC among individuals with chronic hepatitis B or C virus infection [6 -12]. In addition, patients with DM or prediabetes had higher liver cancer mortality rates [13]. However, the impact of DM on the prognosis of patients with HCC remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with impaired glucose metabolism (IGM) or type 2 diabetes might have an increased risk of cancer and cancerrelated mortality [1][2][3][4][5][6][7]. Insulin resistance, hyperglycaemia, high levels of insulin, and production of IGF-I and IGF-II have been suggested to induce tumour cell growth, thereby possibly providing a mechanistic link between glucose metabolism and cancer [1,3,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…None of the studies [1][2][3][4][5][6][7] that reported on the association between glucose metabolism and cancer took proinsulin into account. In the light of recent evidence [14] for the potential link between proinsulin and cancer, proinsulin could explain part of the overall risk of developing cancer.…”
Section: Introductionmentioning
confidence: 99%